PENGARUH KESELAMATAN KERJA, KOMPENSASI, LINGKUNGAN KERJA, TERHADAP TURNOVER INTENTION KARYAWAN HOTEL DI BALI - Ramdhan Kurniawan; I Wayan Pantiyasa; I Wayan Eka Sudarmawan; Ni Wayan Rena Mariani; Laula Dwi Marthika (JURNAL ILMIAH EDUNOMIKA, 2023)
The incidence of high turnover in a company will have a negative impact, namely the instability and uncertainty of the workforce and personnel costs that become larger. Turnover can be caused by various factors, in this study will focus on the influence of work safety, compensation, work environment. Samples were taken as many as 98 respondents from all hotel employees in the Province of Bali. The sample is determined by simple random sampling technique. Data was collected using a questionnaire instrument. The data analysis technique used is the linear regression method using the SPSS application. The results obtained from this study note that all variables have an influence on turnover intention. Occupational safety has a positive and significant effect on turnover intention with a value of 0.000